Design and Test of Lower Part Humanoid Dancer Robot to Do Foot Lifting Move of Remo Dance - Muhammad Hilman Fatoni; Muchammad Ainur Fahd; Djoko Purwanto (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
Development of robotic technology is advancing very rapidly, especially the development of humanoid robots. Humanoid robots have been used for various types of functions in various fields, including in the world of military, medical, industrial, and even in general use through commercial sales. Dancer Robot is one type of robot used to perform certain dances. The dance performed depends on the type of robot. There are dances performed by wheeled robots in groups, and there are also dances performed by humanoid robots. This  study carried out design and testing of humanoid dancer robot’s lower part to do foot lifting and other basic movements of dance. In foot lifting, the lower part of robot must be able to maintain balance and hold the load from the upper part so it does not fall. The distance of lifted foot also must have sufficient height from the floor. Based on robot design, the length of upper legs are 93.62 mm and lower legs are 93.00 mm. Robot able to make stance up to 8.5 cm wide from left to right leg and capable of lifting foot with height 6.5 cm from the floor without falling.Keywords: HMC58831, navigation, robot.